2016
DOI: 10.1177/1558944715627620
|View full text |Cite
|
Sign up to set email alerts
|

Interfascicular Renal Cell Carcinoma Metastasis to the Ulnar Nerve

Abstract: Solid tumor metastasis, although exceedingly rare, must be considered in the differential diagnosis of a patient with previous cancer history presenting with a wrist or hand mass associated with peripheral neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A case report by Grisold et al 15 demonstrated a mononeuropathy caused by intraneural metastasis from a carcinoid tumor. A separate case published by Humphries et al 16 demonstrated a patient with metastatic renal cell carcinoma to the ulnar nerve presenting as a painful mass in the right volar wrist. Another patient with a delayed sciatic nerve metastasis from a surgically removed renal cell carcinoma has been reported by Varin et al 17 Additionally, there is a rare instance of peripheral neuropathy brought on by infiltrative metastatic adenocarcinoma with no apparent primary lesion.…”
Section: Discussionmentioning
confidence: 99%
“…A case report by Grisold et al 15 demonstrated a mononeuropathy caused by intraneural metastasis from a carcinoid tumor. A separate case published by Humphries et al 16 demonstrated a patient with metastatic renal cell carcinoma to the ulnar nerve presenting as a painful mass in the right volar wrist. Another patient with a delayed sciatic nerve metastasis from a surgically removed renal cell carcinoma has been reported by Varin et al 17 Additionally, there is a rare instance of peripheral neuropathy brought on by infiltrative metastatic adenocarcinoma with no apparent primary lesion.…”
Section: Discussionmentioning
confidence: 99%